2013
DOI: 10.1007/s00428-013-1404-6
|View full text |Cite
|
Sign up to set email alerts
|

Complete pathological response is predictive for clinical outcome after tri-modality therapy for carcinomas of the superior pulmonary sulcus

Abstract: The objective was to define the relationship between histopathological changes after pre-operative chemo-radiotherapy (CRT) and clinical outcome following tri-modality therapy in patients with superior sulcus tumours. A retrospective analysis of tumour material was performed in a series of 46 patients who received tri-modality therapy between 1997 and 2007. Median follow-up was 34 months (5-154). Pathological complete response (pCR) was present in 20/46 tumours (43 %). The most common RECIST score after CRT in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…In the few cases of discordance, the agreement was reached by consensus after thorough discussion. Two previous studies have reported a high reproducibility in the assessment of MPR in NSCLC [30,31]. Specimen grossing as retrospectively evaluated for all tumors was for the majority of cases in line with the current IASLC guidelines advising complete inclusion of tumors <3 cm and sampling of at least 1 block per diameter of the tumor bed [ We assessed tumor regression as continuous variables using 1% increments till 10% and in 5% increments in cases showing >10% residual tumor in the primary tumor bed according to IASLC recommendations to calculate the adapted tumor size [16].…”
Section: Tumor Regression Gradementioning
confidence: 94%
“…In the few cases of discordance, the agreement was reached by consensus after thorough discussion. Two previous studies have reported a high reproducibility in the assessment of MPR in NSCLC [30,31]. Specimen grossing as retrospectively evaluated for all tumors was for the majority of cases in line with the current IASLC guidelines advising complete inclusion of tumors <3 cm and sampling of at least 1 block per diameter of the tumor bed [ We assessed tumor regression as continuous variables using 1% increments till 10% and in 5% increments in cases showing >10% residual tumor in the primary tumor bed according to IASLC recommendations to calculate the adapted tumor size [16].…”
Section: Tumor Regression Gradementioning
confidence: 94%
“…Depending on the size of the tumor, up to 58 paraffin blocks have been prepared in one study. 30 Blaauwgeers et al 51 evaluated on average seven blocks per case (range ¼ 3-15). 51 Other studies mostly focused on the histologic features, and little or no detail was provided on the methods of gross processing of tumors.…”
Section: Pathologic Assessment Of Response To Therapymentioning
confidence: 99%
“…30 Blaauwgeers et al 51 evaluated on average seven blocks per case (range ¼ 3-15). 51 Other studies mostly focused on the histologic features, and little or no detail was provided on the methods of gross processing of tumors. [26][27][28]52 Pataer et al 26 identified histologic heterogeneity among submitted sections and suggested to submit at least one section per cm of resected tumor to adequately assess MPR.…”
Section: Pathologic Assessment Of Response To Therapymentioning
confidence: 99%
See 1 more Smart Citation
“…These patients are commonly treated with induction chemoradiation therapy prior to resection in order to reduce the tumor size and increase the chance for surgical resection with free margins. Tumor should be sampled more extensively in order to evaluate the regression as tumors with complete or subtotal regression (<10% of tumor load) have favorable prognosis (13,14). If no microscopical tumor is found in the initially embedded tissue, more extensive sampling needs to be performed for possible detection of small clusters of vital tumor.…”
Section: Handling After Formalin Fixationmentioning
confidence: 99%